The Effect of Rail Defects on Track Impact Factors - Mohammad Fesharaki; Ton-Lo Wang (Salehan Institute of Higher Education, 2016)
This paper investigates the effect of rail surface flaws on track impact factors for different track and vehicle conditions. For this purpose, a three dimensional vehicle and track as an integrated system modelled. The vehicle, consists car body, bogie frames and wheelsets, is able to model displacements in vertical and lateral directions. Hertz nonlinear springs utilized to connect vehicle to track structure and simulate the interaction between vehicle and track subsystems. Track comprises rail, rail pads, sleepers and ballast materials. For each subsystem, matrices of mass, stiffness and damping were formed and then matrices of total vehicle-track system considering their interaction were solved. Using FRA spectral density functions for rail irregularities, response of track with different qualities to train dynamic forces obtained. Rail random irregularities, rail corrugation and rail joint defects as three common rail defects have been considered in this paper. For each defects the influence of different track and train parameters on impact factor has been studied. The results of study indicate substantial effect of the depth and frequency of the rail flaws on impact factors. This paper has also considered the impact of vehicle speed on dynamic forces and found the critical speed for each case.